Wind Science and Engineering Origins, Developments, Fundamentals and Advancements - Solari, Giovanni; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book provides an essential overview of wind science and engineering, taking readers on a journey through the origins, developments, fundamentals, recent advancements and latest trends in this broad field. Along the way, it addresses a diverse range of topics, including: atmospheric physics; meteorology; micrometeorology; climatology; the aerodynamics of buildings, aircraft, sailing boats, road vehicles and trains; wind energy; atmospheric pollution; soil erosion; snow drift, windbreaks and crops; bioclimatic city-planning and architecture; wind actions and effects on structures; and wind hazards, vulnerability and risk. In order to provide a comprehensive overview of wind and its manifold effects, the book combines scientific, descriptive and narrative chapters. The book is chiefly intended for students and lecturers, for those who want to learn about the genesis and evolution of this topic, and for the multitude of scholars whose work involves the wind.
From the dawn of history to the Renaissance -- From the Renaissance to the end of the 19th century -- From the late 19th century to the mid-20th century -- From the mid-20th century to the 3rd millennium.
Keywords: Mechanics, Applied; Solids; Continuum mechanics; Buildings -- Design and construction; Renewable energy sources; Climatology; Atmospheric science; Solid Mechanics; Continuum Mechanics; Building Construction and Design; Renewable Energy; Climate Sciences; Atmospheric Science